The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jmr.2564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Piper cubeba L. essential oil on methicillin‐resistant Staphylococcus aureus: an AFM and TEM study

Abstract: The increasing prevalence of antibiotic-resistant bacteria is creating a real challenge for health care systems worldwide, making the development of novel antibiotics a necessity. In addition to the development of new antibiotics, there is an urgent need for in-depth characterization of the mechanisms of bacterial resistance toward new drugs. Here, we used essential oils extracted in our laboratory from Piper cubeba against methicillin-resistant Staphylococcus aureus ATCC 43300, one of the most prominent antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Understanding the fine ultrastructure of the bacterial cell wall is important to gain insight into bacterial physiology and the mechanism of action of antibiotics against bacteria (40). Using TEM to observe morphological changes in bacterial cells provides useful insights into the mechanism underlying the activity of antibacterial agents (41).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the fine ultrastructure of the bacterial cell wall is important to gain insight into bacterial physiology and the mechanism of action of antibiotics against bacteria (40). Using TEM to observe morphological changes in bacterial cells provides useful insights into the mechanism underlying the activity of antibacterial agents (41).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study with Piper cubeba L. EO, transmission electron microscopy confirmed that this EO caused significant changes in the cell wall; Alharbi et al . suggested that it could potentially impair bacterial activity in S. aureus .…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study with Piper cubeba L. EO, transmission electron microscopy confirmed that this EO caused significant changes in the cell wall; Alharbi et al [21] suggested that it could potentially impair bacterial activity in S. aureus. Cinnamaldehyde in a concentration of 100 lg/ml and geraniol 200 lg/ml against Escherichia coli and the same compounds at 400 and 1450 lg/ml, respectively, against resistant Staphylococcus aureus showed interactions with cell wall similar with our data in C. acnes.…”
Section: Discussionmentioning
confidence: 96%
“…Now, we can see beta-lactamase-producing Letters to Editor bacteria, methicillin-resistant bacteria, and extended methicillin-resistant Staphylococcus aureus. [2] Above said was an example for genetic modification for sustaining life. Similar effect might happen in human genome also, that make our genome resistant against environmental toxins.…”
Section: Incidence Of Malignancy In the Future?mentioning
confidence: 99%